2012
DOI: 10.1007/s00345-012-0921-2
|View full text |Cite
|
Sign up to set email alerts
|

Randomized prospective trial of tubeless versus conventional minimally invasive percutaneous nephrolithotomy

Abstract: No significant differences were found between conventional and tubeless mPCNL in safety issues and stone clearance rate. However, patients treated with tubeless mPCNL had shorter hospitalization stays and were less likely to experience back pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 15 publications
1
21
0
Order By: Relevance
“…A randomized prospective trial evaluated the efficacy and safety of tubeless (JJ stent but no nephrostomy drainage tubes) versus conventional mini-PCNL (JJ stent and drainage tubes). [ 25 ] In this series with 32 patients, the tubeless mini-PCNL group had significantly shorter hospital stays and experienced significantly less back pain than the conventional mini-PCNL group. There were no significant differences in operation time, stone clearance and complications.…”
Section: Techniquementioning
confidence: 88%
“…A randomized prospective trial evaluated the efficacy and safety of tubeless (JJ stent but no nephrostomy drainage tubes) versus conventional mini-PCNL (JJ stent and drainage tubes). [ 25 ] In this series with 32 patients, the tubeless mini-PCNL group had significantly shorter hospital stays and experienced significantly less back pain than the conventional mini-PCNL group. There were no significant differences in operation time, stone clearance and complications.…”
Section: Techniquementioning
confidence: 88%
“…However, routine use in all patients was hypothesised to be a major contributor to patient discomfort and increased LOS. Several studies have since shown the tubeless approach is not only safe and effective, but leads to decreased postoperative pain, analgesia use, LOS and cost . While there have been several series reporting tubeless PCNL to be safe and effective in the elderly (age >60 years) , children (age <16 years) and in patients with renal anomalies , to our knowledge there has been only one study evaluating tubeless PCNL in obese patients.…”
Section: Discussionmentioning
confidence: 99%
“…Leakage and fever were the most common postoperative complications in five patients (7.5%) and six patients (20%), respectively. Hung et al [10] reported leakage in two patients (4.9%) and fever in five patients (12.1%), and Lu et al [11] reported leakage in 3.1% and fever in 15.6% post-MIPNL.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, Chinese minimally invasive (MIPNL) is defined as a PNL technique with small working sheath, which is performed using an 8-9.8 Fr URS through a 16 Fr percutaneous renal access tract, this is technique was used also by other [10,11].…”
Section: Discussionmentioning
confidence: 99%